Participatory science and education: bringing both views into focus. Issue 6 (1st August 2012) - Zoellick, Bill; Nelson, Sarah J; Schauffler, Molly
Abstract : Aligning the goals of scientists and participants becomes more challenging when citizen science moves into middle‐ and high‐school classrooms. Here, we describe a logic model developed in association with the Acadia Learning Project, a collaboration among scientists, teachers, and students that successfully meets both research and educational needs. The logic model is intended to assist other classroom‐based citizen‐science initiatives with project design and evaluation.